Cross-linked sodium hyaluronate gel porous hydroxyapatite microsphere-containing compound and preparation method thereof

By uniformly distributed polyitic hydroxylhhelite micro -balls in the cross -linked hyaluronate gel, the problem of insufficient liquidity and stability caused by the uneven distribution of micro -ball distribution in the existing technology, realizing the applicability of the complex And durability.

CN119367616APending Publication Date: 2025-01-28DEQING AOWITAI BIOTECHNOLOGY CO LTD

Patent Information

Application Number
CN202411520487.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-29
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

In the existing injection gel technology, porous hydroxyapatite microspheres are unevenly distributed in the gel, resulting in insufficient fluidity and stability, which is difficult to meet the actual application needs.

Method used

Through the precise formula ratio and suitable process, the polyitic hydroxyl -based limestone micro -ball is evenly distributed in the cross -linked hyaluronate gel particles to form a complex to ensure its stability and persistence in the body.

Benefits of technology

The polyitic hydroxylhhexylite micro -ball is evenly distributed in the gel, which improves the liquidity and stability of the complex, and is suitable for the application of biomedical fields such as organizational engineering.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119367616A_ABST
    Figure CN119367616A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of injection gel, and discloses a cross-linked sodium hyaluronate gel porous hydroxyapatite microsphere-containing compound and a preparation method thereof. In the cross-linked sodium hyaluronate gel compound containing the porous hydroxyapatite microspheres, the porous hydroxyapatite microspheres are uniformly distributed in cross-linked sodium hyaluronate gel particles with uniform particle size. The cross-linked sodium hyaluronate gel containing the porous hydroxyapatite microsphere compound provided by the invention has excellent mechanical properties, and also has certain durability and stability. The preparation of the cross-linked sodium hyaluronate gel particles enables the porous hydroxyapatite microspheres to be uniformly distributed in the gel particles, and the accurate formula proportion enables the porous hydroxyapatite microspheres to stimulate the generated collagen to gradually start to grow when the cross-linked sodium hyaluronate gel begins to slowly degrade in vivo; therefore, a perfect alternating effect of the cross-linked sodium hyaluronate gel and the porous hydroxyapatite microspheres is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of injection gel, in particular to a cross-linked sodium hyaluronate gel-containing porous hydroxyapatite microsphere composite and a preparation method thereof. Background Art

[0002] Porous hydroxyapatite microspheres (HAP) are widely used as biomedical materials because of their excellent biocompatibility, biodegradability and osteoconductivity. Their porous structure is conducive to cell growth and nutrient exchange, providing an ideal cell scaffold for tissue engineering. Porous hydroxyapatite microspheres are an inorganic substance that is close to the structure of human bones. In addition, porous hydroxyapatite microspheres are different from other types of microspheres in terms of inflammatory stimulation. The porous hydroxyapatite microspheres can provide a larger specific surface area, a lower relative density and better diffusion performance, which is conducive to cell attachment and growth. Their chemical properties have a lower inflammatory stimulation to the body, rather than non-inflammatory stimulation of collagen production. In addition, porous hydroxyapatite microspheres have certain antibacterial properties and can inhibit the growth of pathogenic microorganisms.

[0003] Sodium hyaluronate gel (HA) is a natural polymer material and an important component of skin, synovial fluid and cartilage tissue. It has excellent moisturizing, lubricity, biocompatibility and degradability. Sodium hyaluronate has the function of promoting cell migration and proliferation, which can further enhance the interaction between cells and filler materials. In addition, sodium hyaluronate has anti-inflammatory effects, which can reduce the inflammatory response after tissue damage and help accelerate the adverse reactions caused by the injection of filler materials into the body.

[0004] A Chinese invention patent (publication number: CN118557795A, publication date: 2024.08.30) discloses an injectable cross-linked hyaluronic acid hydroxyapatite gel and a preparation method thereof. An injectable cross-linked hyaluronic acid hydroxyapatite gel comprises a modified sodium hyaluronate hydroxyapatite microsphere gel and a sodium hyaluronate hydroxyapatite microsphere mixed solution, wherein the raw materials of the modified sodium hyaluronate hydroxyapatite microsphere gel comprise the following components in parts by weight: 40-70 parts of hydroxyapatite microspheres, 1-3 parts of hyaluronic acid, 0.1-0.2 parts of a cross-linking agent, and 30-40 parts of a lidocaine solution; the raw materials of the sodium hyaluronate hydroxyapatite microsphere mixed solution comprise the following components in parts by weight: 15-25 parts of hydroxyapatite microspheres and 0.5-1.5 parts of sodium hyaluronate dry powder. In this application, organic acid is used to modify hydroxyapatite, thereby improving the dispersion performance and stability of hydroxyapatite and further reducing the occurrence of precipitation of hydroxyapatite microspheres. Summary of the invention

[0005] In view of the deficiencies in the prior art, the present invention provides a cross-linked sodium hyaluronate gel-containing porous hydroxyapatite microsphere composite and a preparation method thereof. The precise formula ratio and appropriate process enable the porous hydroxyapatite microspheres to be evenly distributed in the cross-linked sodium hyaluronate gel particles, and the composite has balanced fluidity and stability, appropriate viscoelasticity, and is very suitable for practical applications.

[0006] In order to achieve the above-mentioned purpose, the present invention adopts the following technical solutions: A cross-linked sodium hyaluronate gel-containing porous hydroxyapatite microsphere composite, wherein the porous hydroxyapatite microspheres are uniformly distributed in cross-linked sodium hyaluronate gel particles with uniform particle size. The composite is prepared by comprising raw material A and raw material B: raw material A 50-80%, raw material B 20-50%; The raw material A is prepared by mixing cross-linked sodium hyaluronate gel particles and non-cross-linked sodium hyaluronate, and the raw material B is porous hydroxyapatite microspheres; the cross-linked sodium hyaluronate gel is prepared from sodium hyaluronate, sodium hydroxide, a cross-linking agent BDDE and water for injection, and the non-cross-linked sodium hyaluronate is prepared from lidocaine solution and sodium hyaluronate; The porous hydroxyapatite microspheres have a particle size of 25 μm-50 μm, and the cross-linked sodium hyaluronate gel has a particle size of less than 300 microns.

[0007] The appropriate particle size of cross-linked sodium hyaluronate gel will not cause needle clogging, has a good filling effect, and is easier to degrade.

[0008] Porous hydroxyapatite microspheres of 25μm-50μm can ensure their stability and durability in tissues, can effectively combine with surrounding tissues, promote collagen production, and their superstructure is conducive to biodegradation and absorption. Too small a particle size may be cleared more quickly by macrophages, thereby reducing the long-term effectiveness of the product and affecting the fluidity and uniform distribution of the product; too large a particle size may cause needle blockage or inability to inject. The appropriate particle size and morphology enable them to have a strong and stable scaffold structure after injection into the tissue, thereby providing good volume and support effects during the filling process.

[0009] Preferably, the composite comprises raw material A and raw material B: raw material A 50%, raw material B 50%.

[0010] Preferably, the composite comprises raw material A and raw material B: raw material A 70%, raw material B 30%.

[0011] Preferably, the composite comprises raw material A and raw material B: raw material A 80%, raw material B 20%.

[0012] Preferably, the preparation method of the raw material A comprises the following steps: S1. Preparation of cross-linked sodium hyaluronate gel particles: at room temperature, sodium hyaluronate, sodium hydroxide, a cross-linking agent and water for injection are added to a beaker, and the mixture is stirred and dissolved to obtain a sodium hyaluronate gel; the obtained sodium hyaluronate gel is subjected to a cross-linking reaction in an oven, and the cross-linked gel is cut, dialyzed, water-controlled, sieved and granulated, and finally the cross-linked sodium hyaluronate gel is homogenized using a high-speed disperser to obtain cross-linked sodium hyaluronate gel particles with a particle size of less than 300 μm; S2. preparing non-cross-linked sodium hyaluronate: preparing a lidocaine solution with a lidocaine content of 3.00 mg / ml, adding sodium hyaluronate, and stirring to obtain a non-cross-linked sodium hyaluronate solution; S3. Prepare raw material A: mix the cross-linked sodium hyaluronate gel particles and non-cross-linked sodium hyaluronate in a mass ratio of 95:5 to obtain raw material A.

[0013] Preferably, the dialysis comprises the following steps: the cross-linked sodium hyaluronate gel is dialyzed in a primary manner using a phosphate buffer having a pH value of 8-10 and an osmotic pressure of 400-1000 mOsm / L, and the cross-linked sodium hyaluronate gel after the primary dialysis is dialyzed in a secondary manner using a phosphate buffer having a pH value of 6.0-8.0 and an osmotic pressure of 270-350 mOsm / L, and the secondary dialysis is repeated 3 times. Preferably, the temperature of the primary dialysis is 30-40° C. and the time is 2-4 hours.

[0014] Preferably, the crosslinking temperature of the oven is 30°C-70°C, and the crosslinking time is 2-4 hours; The mesh number of the sieving granulation is 300 meshes.

[0015] Preferably, the preparation method of the raw material B comprises the following steps: S1. Prepare a first solution: At room temperature, weigh 10 parts of Ca(NO3)2·4H2O, dissolve it in deionized water, and stir it thoroughly to obtain a first solution; S2. Prepare a second solution: At room temperature, weigh 6 parts of (NH4)2HPO4, dissolve them in deionized water, and stir them thoroughly to dissolve, to obtain a second solution; S3, preparing a third solution: slowly adding the second solution to the first solution, stirring while adding, using ammonia NH3·H2O to adjust the pH to 10-12 to obtain a third solution, and letting it stand for 24 hours; S4, preparing a fourth solution: heating the third solution at 120° C. for 10 h, filtering to remove excess ammonia and impurities, and then washing the solution with deionized water or anhydrous ethanol to obtain a fourth solution; S5, preparing a crude product 1: adding the polyethylene glycol solution to the fourth solution, stirring the mixed solution thoroughly and adding it to a spray dryer, with a spray temperature of 200-210° C., a feed rate of 5-6 mL / min, an air volume of 300 L / h, and a nozzle diameter of 1.0-1.2 mm, to obtain a crude product 1; S6. Prepare crude product 2: place crude product 1 into a muffle furnace for high-temperature calcination at 800°C to obtain crude microsphere product 2; S7. Prepare raw material B: use a sieve to sieve the crude microsphere product 2 to retain microspheres of 25μm-50μm, and finally wash, dry and sterilize to obtain raw material B.

[0016] Furthermore, the present invention also provides a method for preparing the composite, comprising the following steps: S1. Preparing a composite: placing raw material A and raw material B in a static mixer at room temperature and mixing them thoroughly to obtain a composite; S2, degassing treatment: the compound is stirred and degassed by a mixing mixer, and refrigerated and left to stand for 23-25 ​​hours; S3. High-pressure sterilization: The degassing compound is transferred into a pre-filled syringe with a filling capacity of 1 ml or 2 ml. The filled syringe with the compound is then transferred into a high-pressure steam sterilizer for sterilization to obtain the final product.

[0017] Preferably, the power of the static mixer is 7.5 kW and the air inlet pressure is 0.2 MPa; The power of the mixing mixer is 5 kW, the mixing time is 5-10 min, and the rotation speed is 1000-1500 r / min; The temperature of the high pressure steam cooker is 121° C. and the steam sterilization takes 15-20 minutes.

[0018] Porous hydroxyapatite microspheres cannot be directly injected into the human body, and it is necessary to consider adding a suitable gel as a carrier. The applicant finally chose cross-linked sodium hyaluronate gel as a carrier. This design is more considered because cross-linked sodium hyaluronate gel has special viscosity and adhesion properties. Compared with the combination of porous hydroxyapatite microspheres (HAP) and physiological water alone, cross-linked sodium hyaluronate gel as a carrier will not cause precipitation and agglomeration and nodules caused by uneven shaking, and can reduce the irritation of porous hydroxyapatite microspheres to surrounding tissues. And cross-linked sodium hyaluronate gel as a carrier can immediately take effect after injection. Cross-linked sodium hyaluronate gel begins to slowly degrade in the body in about 4-6 weeks and is replaced by its own collagen. At this time, porous hydroxyapatite microspheres begin to play a role. The porous microspheres are wrapped by subcutaneous cells and tissues, stimulating the increase of fibroblasts and promoting the production of collagen, achieving a perfect alternating relay effect between the two, and bringing consumers a better treatment experience. Cross-linked sodium hyaluronate gel wraps around porous hydroxyapatite microspheres to form a semi-solid paste implant, which is easy to inject. When injected into human tissue, these stable and smooth porous hydroxyapatite microspheres form a supporting skeleton, stimulating the growth of type I collagen and type III collagen, which are interlaced in the gaps between the porous hydroxyapatite microspheres. This stable and soft structure results in long-lasting and non-displacement efficacy.

[0019] The cross-linked sodium hyaluronate gel-containing porous hydroxyapatite microsphere composite provided by the present invention has excellent mechanical properties, not only has the good mechanical strength and toughness of the porous hydroxyapatite microspheres, but also has the high viscoelasticity of the cross-linked sodium hyaluronate to improve the ductility and flexibility of the composite material, can meet the requirements of biomedical fields such as tissue engineering for material mechanical properties, and at the same time has certain durability and stability.

[0020] The preparation of cross-linked sodium hyaluronate gel particles allows the porous hydroxyapatite microspheres to be evenly distributed in the gel particles. The precise formula ratio ensures that when the cross-linked sodium hyaluronate gel begins to slowly degrade in the body, the porous hydroxyapatite microspheres stimulate the production of collagen and gradually begin to grow, thereby achieving a perfect alternation between the cross-linked sodium hyaluronate gel and the porous hydroxyapatite microspheres. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 This is a comparison diagram of the microsphere distribution of the composite of the present invention and comparative example 3, with comparative example 3 on the left and the composite of the present invention on the right.

[0022] Figure 2 Scanning electron microscope image of porous hydroxyapatite microspheres (200×).

[0023] Figure 3 Scanning electron microscope image (1500×) of porous hydroxyapatite microspheres.

[0024] Figure 4 This is the infrared spectrum of porous hydroxyapatite microspheres. DETAILED DESCRIPTION

[0025] The following is a clear and complete description of the technical solutions in the embodiments of the present invention in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0026] Example 1 1. Preparation of Raw Material A S1. Preparation of cross-linked sodium hyaluronate gel particles: At room temperature, add 140 ml of 1 wt% sodium hydroxide and 20 g of sodium hyaluronate powder (molecular weight 1.5×10 6 Da), 2600μl BDDE crosslinker, add enough water for injection to meet the concentration of cross-linked sodium hyaluronate gel of 20mg / ml, stir and dissolve thoroughly. Cross-link in an oven at a specific temperature of 30°C for 2 hours to make the sodium hyaluronate gel undergo a cross-linking reaction. Cut the cross-linked sodium hyaluronate gel into pieces, and then use a phosphate buffer with a pH of 8.5 and an osmotic pressure of 480mOsm / L for primary dialysis, the dialysis temperature is 25°C, and the dialysis time is 2 hours. The dialyzed gel is treated with a phosphate buffer with a pH of 6.5 and an osmotic pressure of 300mOsm / L for secondary dialysis 3 times, soaked and dialyzed for 3 hours, and the buffer is controlled and placed in a refrigerator. After that, it is sieved and granulated using a sieve, and finally a high-speed disperser is used for homogenization and micronization to obtain cross-linked sodium hyaluronate gel particles with a particle size of 300 microns.

[0027] S2. Preparation of non-cross-linked sodium hyaluronate: Weigh 0.3 g of lidocaine dry powder and dissolve it in 100 ml of water for injection, shake and dissolve at room temperature until the solution is colorless and transparent, and store at low temperature for later use; weigh 2.0 g of sodium hyaluronate raw material and add it to the above-prepared lidocaine solution to meet the concentration of non-cross-linked sodium hyaluronate of 2.0 mg / ml, shake and dissolve at room temperature until the solution is colorless and transparent, and store at low temperature for later use.

[0028] S3. Prepare raw material A: add non-cross-linked sodium hyaluronate to cross-linked sodium hyaluronate gel particles, and mix the cross-linked sodium hyaluronate gel particles and non-cross-linked sodium hyaluronate in a mass ratio of 95%:5%.

[0029] 2. Preparation of Raw Material B At room temperature, weigh 10 parts of Ca(NO3)2·4H2O, dissolve it in deionized water, and stir it for 30 minutes to dissolve it to obtain the first solution; weigh 6 parts of (NH4)2HPO 4, Dissolve in deionized water, stir thoroughly for 70 minutes to dissolve, and obtain a second solution. Slowly add the second solution to the first solution, stirring while adding, use ammonia (NH3·H2O) to adjust the pH to 11, and obtain a third solution, let it stand for 24 hours, heat the obtained third solution at 120°C for 10 hours, filter to remove excess ammonia and impurities, and then use deionized water or anhydrous ethanol to wash the solution, wash three times, and obtain a fourth solution. The polyethylene glycol solution is added to the obtained fourth solution, and after being fully stirred, the mixed solution is added to a spray dryer with a spray temperature of 200°C, a feed rate of 5 mL / min, an air intake volume of 300 L / h, and a nozzle diameter of 1.2 mm to obtain a crude product 1; the obtained crude product 1 is placed in a muffle furnace for high-temperature calcination at a temperature of 800°C to obtain a crude microsphere product 2; the crude microsphere product 2 is sieved using 325 mesh and 625 mesh sieves in turn to retain microspheres of 30 μm, which are the required porous hydroxyapatite microspheres.

[0030] 3. Preparation of the composite 8 parts of cross-linked sodium hyaluronate gel and 2 parts of porous hydroxyapatite microspheres were placed in a static mixer with a power of 7.5 kW and an air inlet pressure of 0.2 MPa, and mixed to obtain a cross-linked sodium hyaluronate gel containing porous hydroxyapatite microspheres. The material treated by the static mixer was transferred to a mixing and blending machine with a power of 5 kW, a time setting of 7 min, and a speed setting of 1100 rpm for stirring and degassing to fully mix the two, and then the container containing the mixture was wrapped with tin-platinum paper, sealed and placed in a 2-8°C refrigerator for 24 hours. The treated complex was transferred to a prefilled syringe with a filling capacity of 1 ml or 2 ml, and then the prefilled syringe with the complex was transferred to a high-pressure steam sterilizer for sterilization, the sterilization temperature was set to 121°C, and the sterilization time was 15 min, and the result was a cross-linked sodium hyaluronate gel containing porous hydroxyapatite microspheres.

[0031] Example 2 1. Preparation of Raw Material A S1. Preparation of cross-linked sodium hyaluronate gel particles: At room temperature, add 130 ml of 1 wt% sodium hydroxide and 18 g of sodium hyaluronate powder (molecular weight 1.5×10 6Da), BDDE cross-linker 2340μl, add enough water for injection to meet the concentration of cross-linked sodium hyaluronate gel of 18mg / ml, stir and dissolve thoroughly. Cross-link in an oven at a specific temperature of 45°C for 3 hours to make the sodium hyaluronate gel undergo a cross-linking reaction. Cut the cross-linked sodium hyaluronate gel into pieces and perform primary dialysis using a phosphate buffer with a pH of 8.5 and an osmotic pressure of 480mOsm / L. The dialysis temperature is 30°C and the dialysis time is 2 hours. The dialyzed gel is treated with a phosphate buffer with a pH of 6.5 and an osmotic pressure of 300mOsm / L for two secondary dialysis three times, soaked and dialyzed for 3 hours, and the buffer is controlled and placed in a refrigerator. After that, it is sieved and granulated using a sieve, and finally a high-speed disperser is used for homogenization and micronization to obtain cross-linked sodium hyaluronate gel particles with a particle size of 200 microns.

[0032] S2. Preparation of non-cross-linked sodium hyaluronate: weigh 0.3 g of lidocaine dry powder and dissolve it in 100 ml of water for injection, shake and dissolve at room temperature until the solution is colorless and transparent, and store at low temperature for later use; weigh 2.1 g of sodium hyaluronate raw material and add it to the above-prepared lidocaine solution to meet the concentration of non-cross-linked sodium hyaluronate of 2.1 mg / ml, shake and dissolve at room temperature until the solution is colorless and transparent, and store at low temperature for later use.

[0033] S3. Prepare raw material A: add non-cross-linked sodium hyaluronate to cross-linked sodium hyaluronate gel particles, and mix the cross-linked sodium hyaluronate gel particles and non-cross-linked sodium hyaluronate in a mass ratio of 95%:5%.

[0034] 2. Preparation of Raw Material B At room temperature, weigh 10 parts of Ca(NO3)2·4H2O, dissolve it in deionized water, and stir it for 30 minutes to dissolve it to obtain the first solution; weigh 6 parts of (NH4)2HPO 4,Dissolve in deionized water, stir thoroughly for 70 minutes to dissolve, and obtain a second solution. Slowly add the second solution to the first solution, stirring while adding, use ammonia (NH3·H2O) to adjust the pH to 10, and obtain a third solution, let it stand for 24 hours, heat the obtained third solution at 120°C for 11 hours, filter to remove excess ammonia and impurities, and then use deionized water or anhydrous ethanol to wash the solution, wash three times, and obtain a fourth solution. The polyethylene glycol solution is added to the obtained fourth solution, and after being fully stirred, the mixed solution is added to a spray dryer with a spray temperature of 210°C, a feed rate of 6 mL / min, an air intake volume of 300 L / h, and a nozzle diameter of 1.0 mm to obtain a crude product 1; the obtained crude product 1 is placed in a muffle furnace for high-temperature calcination at a temperature of 800°C to obtain a crude microsphere product 2; the crude microsphere product 2 is sieved using 325 mesh and 625 mesh sieves in turn to retain microspheres of 25 μm, which are the required porous hydroxyapatite microspheres.

[0035] 3. Preparation of the composite 7 parts of cross-linked sodium hyaluronate gel and 3 parts of porous hydroxyapatite microspheres are placed in a static mixer with a power of 7.5kW and an air inlet pressure of 0.2 MPa, and mixed to obtain a cross-linked sodium hyaluronate gel containing porous hydroxyapatite microspheres. The material treated by the static mixer is transferred to a mixing mixer with a power of 5kW, a time setting of 6min and a speed setting of 1200r / min, and stirred and degassed to fully mix the two, and then the container containing the mixture is wrapped with tin platinum paper, sealed and placed in a 2-8°C refrigerator for 24 hours. The treated complex is transferred to a pre-filled syringe with a filling capacity of 1ml or 2ml, and then the filling syringe of the cross-linked sodium hyaluronate gel containing porous hydroxyapatite microspheres is transferred to a high-pressure steam sterilizer for sterilization, the sterilization temperature is set to 121°C, and the sterilization time is 15min, and the resulting is a cross-linked sodium hyaluronate containing porous hydroxyapatite microspheres complex.

[0036] Example 3 1. Preparation of Raw Material A S1. Preparation of cross-linked sodium hyaluronate gel particles: At room temperature, add 130 ml of 1 wt% sodium hydroxide and 18 g of sodium hyaluronate powder (molecular weight 1.5×10 6Da), 2340μl BDDE crosslinker, add enough water for injection to meet the concentration of cross-linked sodium hyaluronate gel of 18mg / ml, and stir thoroughly to dissolve. Cross-link in an oven at a specific temperature of 55°C for 4 hours to make the sodium hyaluronate gel undergo a cross-linking reaction. Cut the cross-linked sodium hyaluronate gel into pieces and perform primary dialysis using a phosphate buffer with a pH of 8.5 and an osmotic pressure of 480mOsm / L. The dialysis temperature is 40°C and the dialysis time is 2 hours. The dialyzed gel is treated with a secondary dialysis of phosphate buffer with a pH of 6.5 and an osmotic pressure of 300mOsm / L for 3 times, soaked and dialyzed for 3 hours, and the buffer is controlled and placed in a refrigerator. After that, it is sieved and granulated using a sieve, and finally a high-speed disperser is used for homogenization and micronization to obtain cross-linked sodium hyaluronate gel particles with a particle size of 100 microns.

[0037] S2. Preparation of non-cross-linked sodium hyaluronate: Weigh 0.3 g of lidocaine dry powder and dissolve it in 100 ml of water for injection, shake and dissolve at room temperature until the solution is colorless and transparent, and store at low temperature for later use; weigh 2.2 g of sodium hyaluronate raw material and add it to the above-prepared lidocaine solution to meet the concentration of non-cross-linked sodium hyaluronate of 2.2 mg / ml, shake and dissolve at room temperature until the solution is colorless and transparent, and store at low temperature for later use.

[0038] S3. Prepare raw material A: add non-cross-linked sodium hyaluronate to cross-linked sodium hyaluronate gel particles, and mix the cross-linked sodium hyaluronate gel particles and non-cross-linked sodium hyaluronate in a mass ratio of 95%:5%.

[0039] 2. Preparation of Raw Material B At room temperature, weigh 10 parts of Ca(NO3)2·4H2O, dissolve it in deionized water, and stir it for 30 minutes to dissolve it to obtain the first solution; weigh 6 parts of (NH4)2HPO 4,Dissolve in deionized water, stir thoroughly for 70 minutes to dissolve, and obtain a second solution. Slowly add the second solution to the first solution, stirring while adding, use ammonia (NH3·H2O) to adjust the pH to 10, and obtain a third solution, let it stand for 24 hours, heat the obtained third solution at 120°C for 11 hours, filter to remove excess ammonia and impurities, and then use deionized water or anhydrous ethanol to wash the solution, wash three times, and obtain a fourth solution. The polyethylene glycol solution is added to the obtained fourth solution, and after being fully stirred, the mixed solution is added to a spray dryer with a spray temperature of 210°C, a feed rate of 6 mL / min, an air intake volume of 300 L / h, and a nozzle diameter of 1.0 mm to obtain a crude product 1; the obtained crude product 1 is placed in a muffle furnace for high-temperature calcination at a temperature of 800°C to obtain a crude microsphere product 2; the crude microsphere product 2 is sieved using 325 mesh and 625 mesh sieves in turn to retain microspheres of 25 μm, which are the required porous hydroxyapatite microspheres.

[0040] 3. Preparation of the composite Place 5 parts of cross-linked sodium hyaluronate gel and 5 parts of porous hydroxyapatite microspheres in a static mixer with a power of 7.5kW and an air inlet pressure of 0.2 MPa, and mix to obtain a cross-linked sodium hyaluronate gel containing porous hydroxyapatite microspheres. The material treated by the static mixer is transferred to a mixing mixer with a power of 5kW, a time setting of 6min and a speed setting of 1200 rpm, and stirred and degassed to fully mix the two. Then, the container containing the mixture is wrapped with tin-platinum paper, sealed and placed in a 2-8°C refrigerator for 24 hours. The treated complex is transferred to a prefilled syringe with a filling capacity of 1ml or 2ml, and then the prefilled syringe with the complex is transferred to a high-pressure steam sterilizer for sterilization. The sterilization temperature is set to 121°C and the sterilization time is 15min. The result is a cross-linked sodium hyaluronate containing porous hydroxyapatite microspheres complex.

[0041] Comparative Example 1 The formula and preparation refer to Example 3, except that the ratio of the cross-linked sodium hyaluronate gel to the porous hydroxyapatite microspheres is 4:6.

[0042] Comparative Example 2 The formula and preparation refer to Example 1, except that the ratio of the cross-linked sodium hyaluronate gel to the porous hydroxyapatite microspheres is 9:1.

[0043] Comparative Example 3 Provided is a cross-linked hyaluronic acid hydroxyapatite gel, which is prepared according to Example 11 in Chinese invention patent CN118557795A.

[0044] The above embodiments and comparative examples were subjected to performance tests.

[0045] 1. Pushing force performance In this experiment, the syringe push rod is pushed at a constant speed. During the experiment, the injection needle is installed to simulate actual use. The push rod is pushed at a constant speed, and the suspension in the syringe is squeezed out through the needle to obtain the pushing force curve. The pushing force curve shows the change of the pushing force during the sample extrusion process. The numerical results of the average pushing force in the platform area of ​​the pushing force curve are shown in Table 1. Taking a 1ml pre-filled syringe as an example, a small amount of air is discharged from the front end of the syringe, and then it is installed on the detection equipment, the test distance is set to full scale, the pushing speed is set to 30mm / min, the pushing force is set according to the prescribed method, and the value of the average pushing force in the platform area of ​​the pushing force curve is recorded.

[0046] Pushing force performance test A: Set the universal material testing machine pushing speed to 30mm / min; gauge length 30.00mm maximum force / N; prefilled syringe capacity 1ml, use 27G needle.

[0047] Pushing force performance test B: Set the universal material testing machine pushing speed to 30mm / min; gauge length 30.00mm maximum force / N; prefilled syringe capacity 2ml, use 25G needle.

[0048] Table 1 Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Comparative Example 3 Pushing force performance test A 8.5N 15N 22N 28N 6N 7N Pushing force performance test B 12N 18N 26N 30N 10N 10N When the pushing force is small, the sample is easily squeezed out; when the pushing force is large, the sample is not easily squeezed out.

[0049] 2. Particle size test Table 2 D10 D50 D90 Example 1 25μm 180μm 300μm Example 2 25μm 150μm 200μm Example 3 25μm 120μm 100μm 3. Breakage rate test A material tester was used to gradually increase the pressure on the microsphere sample by 5 N each time with a starting pressure of 10 N until the microspheres began to break or deform. The percentage of broken microspheres in the sample was calculated to obtain the breakage rate. The results are shown in Table 3.

[0050] Table 3 Breakage rate under mechanical stress Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Comparative Example 3 Test 1 6.2% 6.5% 6.7% 7.0% 5.8% 6.5% Test 2 7.0% 7.0% 7.5% 7.7% 6.3% 7.0% 4. Mechanical properties test Viscosity test method: Place the mixture sample on the test platform of the rheometer, set the temperature to 37°C to simulate the use conditions, and test at different shear rates, with the highest shear rate being 1 s -1 , low shear rate of 10 s -1. Record the viscosity value, draw the shear rate-viscosity curve, and analyze the rheological behavior of the sample. Viscosity is positively correlated with the microsphere content. When the microsphere content is high, the viscosity of the mixture is high and the fluidity is poor; conversely, when the microsphere content is low, the viscosity is low and the fluidity is good.

[0051] Elastic modulus (G'): Place the sample between the upper and lower plates of the rheometer and select the appropriate test geometry (e.g., flat plate, cone plate). Set a constant frequency (1 Hz) and apply an oscillating load over a range of stresses or strains. Measure and record the elastic response of the sample during the oscillation, i.e., the storage modulus G'. The elastic modulus indicates the structural strength and stability of the mixture. As the microsphere content increases, the G' value increases, the mixture becomes more stable, but the fluidity decreases.

[0052] Viscous modulus (G''): Similar to the elastic modulus test, the viscous response of the material is tested by applying an oscillating stress or strain. The loss modulus G'' is recorded, which reflects the viscous behavior of the material. Set a constant frequency (1 Hz) and test at different frequencies or stress / strain ranges to analyze its viscous properties. The viscous modulus reflects the dissipated energy of the material and is related to flowability. Lower G'' values ​​indicate that the mixture flows more easily.

[0053] Loss factor (tanδ = G'' / G'): Measures the balance between viscosity and elasticity.

[0054] Table 4 Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Comparative Example 3 Viscosity (Pa·s) 2000 2500 3000 4000 1500 1700 Elastic modulus G' (Pa) 120 200 250 300 70 100 Viscous modulus G'' (Pa) 100 160 200 250 50 60 Loss factor (tanδ) 0.85 0.7 0.65 0.55 1.0 0.6 It can be seen from Table 4 that the viscosity of Example 1 is greater than that of Comparative Example 2, and the fluidity of Example 1 is not as good as that of Comparative Example 2, but Example 1 has better stability and a lower breakage rate. The viscosity of Example 2 is smaller than that of Comparative Example 1, and although the stability is lower than that of Comparative Example 1, the fluidity is better, the overall performance is more balanced, and it is more suitable for practical operation. From the comprehensive judgment of Tables 1-4, it can be seen that Example 1 has the best comprehensive performance and shows the best balance in terms of fluidity and stability.

[0055] 5. Release rate of porous hydroxyapatite microspheres Referring to the test method of Chinese invention patent CN118557795A, we took 1 ml of the prepared samples with different mixing ratios and injected them into the prepared 10 ml saline solution. After the samples were injected with saline solution, they were tested at 80 rpm / min on a 37°C constant temperature shaker. The samples were taken out every 7 days and supplemented with an equal volume of saline solution after the samples were removed to keep the total volume constant. The initial gel weight was recorded as a. After the gel was left to stand for 28 days, the weight of the remaining sample was measured as b, and the release rate of the porous hydroxyapatite microspheres was calculated as c=ab / a*100%.

[0056] Table 5 Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Comparative Example 3 Release rate c (%) 0.90 0.95 1.02 1.05 1.07 1.23 As can be seen from Table 5, the release rates of the examples are generally smaller, the gel dissolves more slowly, and the effectiveness of the complex is more lasting.

[0057] The above is a description of the embodiments of the present invention. Through the above description of the disclosed embodiments, professionals and technicians in the field can implement or use the present invention. Various modifications to these embodiments will be apparent to professionals and technicians in the field. The general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to these embodiments shown in this article, but will conform to the widest range consistent with the principles and novelties disclosed herein.

Claims

1. A cross-linked sodium hyaluronate gel-containing porous hydroxyapatite microsphere composite, characterized in that: The porous hydroxyapatite microspheres are evenly distributed in the cross-linked sodium hyaluronate gel particles with uniform particle size. The composite comprises raw material A and raw material B: raw material A 50-80%, raw material B 20-50%; The raw material A is prepared by mixing cross-linked sodium hyaluronate gel particles and non-cross-linked sodium hyaluronate, and the raw material B is porous hydroxyapatite microspheres; the cross-linked sodium hyaluronate gel is prepared from sodium hyaluronate, sodium hydroxide, a cross-linking agent BDDE and water for injection, and the non-cross-linked sodium hyaluronate is prepared from lidocaine solution and sodium hyaluronate; The porous hydroxyapatite microspheres have a particle size of 25 μm-50 μm, and the cross-linked sodium hyaluronate gel has a particle size of less than 300 microns.

2. The composite according to claim 1, characterized in that The composite comprises raw material A and raw material B: raw material A 50%, raw material B 50%.

3. The composite according to claim 1, characterized in that The composite comprises raw material A and raw material B: raw material A 70%, raw material B 30%.

4. The composite according to claim 1, characterized in that The composite comprises raw material A and raw material B: raw material A 80%, raw material B 20%.

5. The composite according to any one of claims 1 to 4, characterized in that: The preparation method of the raw material A comprises the following steps: S1. Preparation of cross-linked sodium hyaluronate gel particles: at room temperature, sodium hyaluronate, sodium hydroxide, a cross-linking agent and water for injection are added to a beaker, and the mixture is stirred and dissolved to obtain a sodium hyaluronate gel; the obtained sodium hyaluronate gel is subjected to a cross-linking reaction in an oven, and the cross-linked gel is cut, dialyzed, water-controlled, sieved and granulated, and finally the cross-linked sodium hyaluronate gel is homogenized using a high-speed disperser to obtain cross-linked sodium hyaluronate gel particles with a particle size of less than 300 μm; S2. preparing non-cross-linked sodium hyaluronate: preparing a lidocaine solution having a lidocaine content of 3.00 mg / ml, adding sodium hyaluronate, and stirring to obtain a non-cross-linked sodium hyaluronate solution; S3. Prepare raw material A: mix cross-linked sodium hyaluronate gel particles and non-cross-linked sodium hyaluronate in a mass ratio of 95:5 to obtain raw material A.

6. The composite according to claim 5, characterized in that The dialysis comprises the following steps: performing primary dialysis on the cross-linked sodium hyaluronate gel using a phosphate buffer having a pH value of 8-10 and an osmotic pressure of 400-1000 mOsm / L, performing secondary dialysis on the cross-linked sodium hyaluronate gel after the primary dialysis using a phosphate buffer having a pH value of 6.0-8.0 and an osmotic pressure of 270-350 mOsm / L, and repeating the secondary dialysis 3 times; Preferably, the temperature of the primary dialysis is 30-40°C and the time is 2-4 hours.

7. The composite according to claim 5, characterized in that The crosslinking temperature of the oven is 30°C-70°C, and the crosslinking time is 2-4 hours; The mesh number of the sieving granulation is 300 meshes.

8. The composite according to any one of claims 1 to 4, characterized in that: The preparation method of the raw material B comprises the following steps: S1. Prepare a first solution: At room temperature, weigh 10 parts of Ca(NO3)2·4H2O, dissolve it in deionized water, and stir it thoroughly to obtain a first solution; S2. Prepare a second solution: At room temperature, weigh 6 parts of (NH4)2HPO4, dissolve them in deionized water, and stir them thoroughly to obtain a second solution; S3, preparing the third solution: slowly adding the second solution into the first solution, stirring while adding, using ammonia NH3·H2O to adjust the pH to 10-12, to obtain the third solution, and letting it stand for 24 hours; S4, preparing a fourth solution: heating the third solution at 120° C. for 10-11 hours, filtering to remove excess ammonia and impurities, and then washing the solution with deionized water or anhydrous ethanol to obtain a fourth solution; S5, preparing a crude product 1: adding the polyethylene glycol solution to the fourth solution, stirring the mixed solution thoroughly and adding it to a spray dryer, with a spray temperature of 200-210° C., a feed rate of 5-6 mL / min, an air volume of 300 L / h, and a nozzle diameter of 1.0-1.2 mm, to obtain a crude product 1; S6. Prepare crude product 2: place crude product 1 into a muffle furnace for high-temperature calcination at 800°C to obtain crude microsphere product 2; S7. Prepare raw material B: use a sieve to sieve the crude microsphere product 2 to retain microspheres of 25μm-50μm, and finally wash, dry and sterilize to obtain raw material B.

9. The method for preparing the composite according to any one of claims 1 to 4, characterized in that: The following steps are involved: S1. Preparing a composite: placing raw material A and raw material B in a static mixer at room temperature and mixing them thoroughly to obtain a composite; S2, degassing treatment: the composite is stirred and degassed by a vacuum planetary stirring degassing machine, and refrigerated and left to stand for 23-25 ​​hours; S3. High-pressure sterilization: The degassing compound is transferred into a pre-filled syringe with a filling capacity of 1 ml or 2 ml. The filled syringe with the compound is then transferred into a high-pressure steam sterilizer for sterilization to obtain the final product.

10. The preparation method according to claim 9, characterized in that: The inlet pressure of the static mixer is 0.2 MPa; The mixing time of the vacuum planetary stirring defoamer is 5-10min, and the rotation speed is 1000-1500r / min; The temperature of the high pressure steam cooker is 121° C., 0.6 MPa, and the steam sterilization takes 15-20 minutes.

Citation Information

Patent Citations

  • Injectable cross-linked hyaluronic acid hydroxyapatite gel and preparation method thereof

    CN118557795A

  • Injection type gel composition as well as preparation method and application thereof

    CN115137877A

  • Human body soft tissue filling material and preparation method thereof

    CN116570765A

  • Hydroxyapatite microspheres and preparation method thereof

    CN117185266A

  • Preparation method of lidocaine hydrochloride-containing sodium hyaluronate gel for injection

    CN117224738A

Cited By

  • Composite hydrogel, preparation method thereof and facial filling medical device

    CN121466381A